Solvability of some integro-differential equations with anomalous diffusion in higher dimensions. Issue 1 (2nd January 2021) - Vougalter, Vitali
ABSTRACT: The article deals with the studies of the existence of solutions of an integro-differential equation in the case of the anomalous diffusion with the negative Laplace operator in a fractional power in R d, d = 4, 5. The proof of the existence of solutions relies on a fixed point technique. Solvability conditions for non Fredholm elliptic operators in unbounded domains are used.